TINJAUAN ETIKA BISNIS ISLAM PADA STRATEGI MARKETING BMH KEDIRI DI TENGAH PANDEMI COVID-19 - Mohammad Basid Alharis (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2020)
Islam does not forbid its servants from doing business in the world. The difference between Islamic business and others is its motivation. In addition to worldly, but the business of Islam is also for the benefit of ukhrowi. And the main goal is not just profit, but zakat and blessing of the results of his efforts. However, business is not always lucky continuously, sometimes experiencing losses due to various factors. Especially at this time, the non-technical factor that is faced now is the impact of the 2019 (covid-19) coronavirus disease pandemic greatly affecting the economies of all Countries in the World. It is interesting to study how the marketing strategy of the company or also business people in order to survive in the midst of this pandemic. Generally affected, the Charitable Institution namely Baitul Maal Hidayatullah (BMH) Kediri has increased incomes. Thus, researchers are interested in conducting a study of Islamic business ethics review on BMH Kediri's marketing strategy in the midst of the covid-19 pandemic. This research uses a qualitative descriptive approach. Because the object of this research is field research, so qualitative research aims to explain phenomena profusely through data collection. The data in this study use primary data through in-depth interviews.